Sexual network characteristics, condomless anal intercourse, and the HIV care cascade among MSM living with controlled versus uncontrolled HIV infection in Lima, Peru: a population-based cross-sectional analysisResearch in context - Carlyn L. Harris; Cherie S. Blair; Eddy R. Segura; Jessica Gutiérrez; Jordan E. Lake; Robinson Cabello; Jesse L. Clark (Elsevier, 2024)
Summary: Background: Despite high rates of HIV transmission among men who have sex with men (MSM) in Lima, Peru, limited data exist on the sexual network characteristics or risk factors for secondary HIV transmission among MSM with uncontrolled HIV infection. We report the frequency of serodiscordant, condomless anal intercourse (CAI) and associated sexual network characteristics among MSM in Lima with detectable HIV viremia and compare to those with undetectable viremia. Methods: This cross-sectional analysis includes MSM who tested positive for HIV-1 during screening for a trial of partner management and STI control (June 2022-January 2023). Participants were tested for HIV, gonorrhoea, chlamydia, and syphilis, and completed questionnaires on their demographic characteristics, sexual identity and behaviour, sexual network structures and engagement in HIV care. Findings: Of 665 MSM, 153 (23%) had detectable (>200 copies/mL) viremia. 75% (499/662) of men living with HIV were previously diagnosed, with 94% (n = 469/499) reporting that they were on ART, and 93% (n = 436/469) virally suppressed. 96% (n = 147/153) of men with detectable viremia reported serodiscordant CAI with at least one of their last three sexual partners, and 74% (n = 106/144) reported the same with all three of their recent partners. In contrast, 62% (n = 302/489) of men with undetectable viral load reported serodiscordant CAI with all of their last three partners (p < 0.01). Interpretation: 23% of men living with HIV in Peru had detectable viremia, of whom almost all (96%) reported recent serodiscordant CAI. The primary gap in the HIV care cascade lies in awareness of HIV serostatus, suggesting that improved access to HIV testing could be a key prevention strategy in Peru. Funding: Funding for this study was provided by NIH/NIMH grants R01 MH118973 (PI: Clark) and R25 MH087222 (PI: Clark).